Análisis de protecciones para sobrecorrientes y sobretensiones en una subestación eléctrica de 69/13.8 KV, 16/24 MVA. Utilizando DIGSILENT Y ATPDRAW. - Vera Suárez, Diego Alejandro (2021)
The work presented in this paper contemplates the analysis of overcurrent and overvoltage protections in a three-phase distribution substation (69 KV / 13.8 KV - 12 / 16 MVA), air-insulated (AIS), using mathematical modeling for the power transformer, circuit breakers, reclosers, fuses, overcurrent relay, current differential relay and surge arresters, using DigSilent short-circuit analysis computational tools and for simulations of overcurrent and overvoltage protection, circuit breakers , reclosers , fuses , overcurrent relay , current differential relay and surge arresters , using computational tools for short circuit analysis DigSilent and for transient voltage and current simulations in ATP Draw.